INVERSE GAS-CHROMATOGRAPHY STUDY OF N-ALCOHOLS-POLY(ACRYLONITRILE-CO-METHYLACRYLATE) SYSTEMS - COSKUN, M; OZDEMIR, E; CELIK, S; CANSIZ, A (Marcel Dekker Inc, 1994)
Inverse gas chromatographic studies have been carried out on systems consisting of acrylonitrile (91.9%)-methylacrylate(8.9 degrees) copolymer and ethanol, 1-propanol, 1-butanol, 1-pentanol, and 1-hexanol as probes. Molar heats(Delta Hs), free energies(Delta Gs) of sorption, Flory-Huggins chi parameters and weight fraction activity coefficients(a(1)/w(1))infinity, were computed for these systems in the range 110-140 degrees C, above glass transition temperature of the copolymer. The solubility parameter of the copolymer at 25 degrees C was estimated from data in the temperature range of 110-140 degrees C. Molar heats of vaporization of n-alcohol probes(Delta Hv) were determined from gas chromatograghic data and the results compared with those of calculated using critical temperatures, boiling temperatures, and molar heats of vaporization of the probes at boiling temperatures.
Keywords: Solubility Parameters; Polymers